Implementasi Model Pembelajaran Numbered Head Together Berbantuan Media Roda Putar untuk Meningkatkan Hasil Belajar Siswa - Anita Rahmawati; Erik Aditia Ismaya; Mila Roysa (Journal on Education, 2020)
This study aims to improve student learning outcomes of student, and teacher teaching skills. Subject to be taught in this study are Social Sciences and Indonesia Language through the Numbered Head Together model, which is assisted by a Turning Wheel media. Learning outcomes are the ability of the skilss, attitude and skills that students get after they receive the tratment given by the teacher so that they can contribute that knowledge in their daily lives. Numbered Head Together learning media are learning process activities where each student is grouped and numbered in the head of activeness of students in searching, processing repoting information in class so that students can go to the front of the class or be presented and report information that has been learned at this time. Spinning Wheel learning media is a media in the form of a wheel or circle which is divided into several sections in which there are questions, this media can attract attention, interest, and motivation to learn so that the learning process will be fun and optimal. The subjects in this study were students of class V SD 2 Tenggeles, totaling 34 students consisting of 20 female students and 14 male students.